Avaliação do semissintético isodilapiol na expressão de genes de resistência a inseticidas em mosquitos Aedes (Stegomyia) aegypti - Lima, Valdirley de Souza (Instituto Nacional de Pesquisa da Amazônia - INPA, 2015)
A. aegypti is the main vector of dengue and other arboviruses in the world. The vector control measures use synthetic insecticides, which cause resistance in this mosquito. The compound Dilapiolle, found in essential oils of the plant Piper aduncum of the Piperaceae family, has been effective as a biopesticide against A. aegypti. In this study, Isodilapiol, derived from the semisynthetic Dilapiolle was evaluated for its potential to induce differential expression of pesticide resistance genes (GSTE7 and P450-12) in the 3rd stage larvae of A. aegypti. The immature forms were collected in the Cidade Nova neighborhood (3 ° 1 '21.36 "S and 59 58' 5,32''O), Manaus, AM, and sent to the Laboratory of Malaria and Dengue / INPA. The immature ones completed their development and the adults, after the cross, gave rise to three successive generations (G1, G2, G3) in order to minimize the environmental variations. The toxicological tests with 2KL-15 started from G4 (4th generation). 3rd stage larvae of A. aegypti were exposed to four concentrations (20, 40, 60 and 80 μg / ml) of 2KL-15 for 4 hours. The larvae were frozen in liquid N2 and stored in a freezer at -80°C. These treatments were repeated to form the next generations: G5, G6 and G7. The extraction and purification of total RNA was performed with the Quiagen® extraction kit, and the complementary strand of mRNA (cDNA) with the kit Promega®. The primers of GSTE7 and P450-12 genes were designed with software "Gene Runner" and Primer3. The qRT-PCR method was performed according to the protocol SYBR Green® Master Mix (Applied Biosystems®) adapted for A. aegypti, and amplifications occurred in the thermal cycler ABI-7500™ Real-Time PCR System, Applied Biosystems®. We observed a differential expression of GSTE7 and P450-12 genes in four concentrations (20, 40, 60 and 80 μg / mL) in generation G4, G5, G6 and G7. However, the major peaks was observed at a concentration of 20 μg / ml, and the gene expression peaks were seen in G4, G5, G6 and G7. The P450-12 gene was differentially expressed when compared to GSTE7. The P450-12 gene might cause oxidative stress in the 3rd larval stage of Ae. aegypti revealing a compound potential effect on the control of A. aegypti, the dengue vector.
Keywords: Expressão Gênica; Isodilapiol; Aedes Aegypti